2014
DOI: 10.1002/psc.2708
|View full text |Cite
|
Sign up to set email alerts
|

Peptide IDR‐1018: modulating the immune system and targeting bacterial biofilms to treat antibiotic‐resistant bacterial infections

Abstract: Host defense (antimicrobial) peptides, produced by all complex organisms, typically contain an abundance of positively charged and hydrophobic amino acid residues. A small synthetic peptide termed innate defense regulator (IDR-)1018 was derived by substantial modification of the bovine neutrophil host defense peptide bactenecin. Here, we review its intriguing properties that include anti-infective, anti-inflammatory, wound healing, and anti-biofilm activities. It was initially developed as an immune modulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 36 publications
2
156
0
4
Order By: Relevance
“…Interestingly, the peptide alone stimulated BMDMs to increase MCP-1 levels comparable to those induced by HKCA treatment. These results are consistent with other studies investigating IDR-1018 in different experimental designs (17,(29)(30)(31). Although our study used a different cell type and inflammatory stimulus, our results indicated that IDR-1018 acts as an anti-inflammatory agent by suppressing proinflammatory cytokines in murine BMDMs challenged with HKCA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the peptide alone stimulated BMDMs to increase MCP-1 levels comparable to those induced by HKCA treatment. These results are consistent with other studies investigating IDR-1018 in different experimental designs (17,(29)(30)(31). Although our study used a different cell type and inflammatory stimulus, our results indicated that IDR-1018 acts as an anti-inflammatory agent by suppressing proinflammatory cytokines in murine BMDMs challenged with HKCA.…”
Section: Discussionsupporting
confidence: 92%
“…Innate defense regulator 1018 (IDR-1018) is a 12-amino-acid distantly related peptide variant of bovine HDP Bac2A, designed for improved immunomodulatory activity, besides direct activity, as well as enhancement of antibiotic action against multidrugresistant bacteria and a broad spectrum of bacterial biofilms, protection against cerebral malaria, and preservation of osseointegration (14)(15)(16)(17). However, to date, the activity of this peptide against human-pathogenic fungi had not been described.…”
mentioning
confidence: 99%
“…Peptide 1018 was subsequently shown to induce killing of bacteria present within oral multispecies biofilms [35], therefore identifying a promising role of this agent for plaque disinfection in dentistry. It is worth mentioning that, like LL-37, peptide 1018 (also termed IDR-1018) is a potent modulator of innate immunity and as such is able to suppress inflammation and enhance protective immunity in several animal infection models [36]. …”
Section: Synthetic Antibiofilm Peptidesmentioning
confidence: 99%
“…Innate defense regulator peptide-1018 (IDR-1018) is a synthetic 12-amino acid derivative of bactenecin, a bovine HDP [42]. IDR-1018 can directly kill bacteria [42], can modulate differentiation and activation of macrophages and neutrophils, thereby regulating their production of chemokines and cytokines [1,26,30,32,37,42], can reduce soft tissue infections [1,37], and can disrupt bacterial biofilms [25,35]. IDR-1018 was chosen as the focus of this study because it is the most potent IDR that has been described [37] and is therefore an attractive agent to potentially reduce orthopaedic infections and inflammatory osteolysis around orthopaedic implants.…”
Section: Introductionmentioning
confidence: 99%